ANALISIS DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - CITRA DEWANTI, HANA; HANDAYANI, SUSI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of liquidity, profitability, investment decisions, financing decisions, and dividend policy on firm value. The sample in this study is manufacturing companies that listed on Indonesian Stock Exchange with the observation period 2014-2017. The sample was selected using judgment sampling technique and obtained 48 companies. The analysis technique used in this study is multiple linear regression analysis using IBM SPSS Statistics 24 program. The results of this study show that profitability, investment decisions and funding decisions have a positive effect on firm value and liquidity has a negative effect on firm value. Then, dividend policy does not affect the value of the company.